A new species of Halophytophilus Brian, 1919 (Copepoda: Harpacticoida: Ectinosomatidae) from cold-water corals in the Porcupine Seabight (NE Atlantic) - Gheerardyn, Hendrik; Seifried, Sybille; Vanreusel, Ann (Zootaxa, 2008)
The first deep-sea representative of Halophytophilus Brian, 1919 is described from samples of dead cold-water coral fragments, glass sponge skeletons and underlying sediment collected from the Porcupine Seabight (NE Atlantic). Halophytophilus lopheliae sp. nov. can be distinguished from its congeners by the dimensions of the P1 endopod and the position of the inner seta on its proximal segment. Moreover, we present the first description of a male in this genus. The occurrence of Halophytophilus and three other ectinosomatid genera with prehensile first legs is remarkable in the deep sea and an indication that the hard substrates of the coral degradation zone may provide an exceptional habitat. A key to the five species of Halophytophilus is included.